(untitled) (Historia, 2021)
Professional historians have proved resistant to the claims of postmodernism, which they see as highly theoretical, rather theatrical and decidedly threatening. As a result, the debate has become polarised, with proponents of postmodernism dismissing traditional historians as "positivist troglodytes", while reconstructionist and constructionist historians speak in "historicidal" terms of deconstructionism.